Who Allowed You To Observe? A Reflexive Overt Organizational Ethnography - Buscatto, Marie (Qualitative Sociology Review, 2008)
Observing people working within organizational contexts through time creates epistemological issues, more so when doing it overtly, with top management’s official agreement. Power relations as well as hierarchical structures strongly influence the way people view the observer and interact with her in organizations. Those interactions also partly depend on his personal background – sex, age, professional position and so on. Following a reflexive approach, my objective is here to better grasp how top management’s agreement to the ethnographer’s entry on the field may influence both the way workers from differing hierarchical levels behave with her (and thus affect her observing conditions) and how he may analyse his ethnographic notes to develop scientific sociological results.